INNOVATIVE DEVELOPMENT OF RUSSIAN AND RESOURCE CENTER NORTH RESOURCES - Vladimir Selin; Vyacheslav Tsukerman (Модернизация, инновация, развитие, 2015)
Included in the international division of labor and take it high competitive position, being technologically outdated, impossible. In this regard, it is considered almost the most important question of the transition from resource-based economy to an innovation.